(untitled) (Biological Sciences - PJSIR, 1997)
The electron impact mass spectral studies on some nitrobenzylidene thioacetal derivatives showed two different mechanisms of oxygen transfer from the nitro group to the sulfur containing fragments via intra-and inter-oxygen transfer. The two mechanisms are mainly dependent on the position of the nitro group. The relative intensity of the sulfoxonium ion formed via an intra-mechanism is always higher than formed by an inter-oxygen transfer mechanism. The oxygen transfer processes were totally eliminated when a free carboxylic group was introduced in the -position to the sulfur atom which faci litates hydrogen transfer from the carboxylic group to the sulfur atom, giving rise to the base peak in their mass spectra as the thioglycolic acid fragment ion rather than the sulfoxonium fragment ion. The presence of two nitro groups, substituted at 2-and 4-positions of the benzylidene nucleus neither increased the relative intensity of the sulfoxonium ion nor competed with the hydrogen transfer mechanism. Conversion of the carboxylic acid into the methyl ester, however, decreased the hydrogen transfer process.